2019
DOI: 10.34234/ded.507761
|View full text |Cite
|
Sign up to set email alerts
|

Değerler Eğitimi Dergisi’nin Bibliyometrik Profili (2009-2018)

Abstract: Bilimsel dergiler, üretilen bilginin bilimsel ağ ile paylaşıldığı akademik ortamlardır. Dergiler bilimsel iletişim dizgesinde bağ kurmaya ve alanyazın oluşturmaya katkıda bulunur. Bu nedenle bilimsel dergilerin bibliyometrik özellikler açısından incelenmesi son derece önemlidir. Bu çalışmada değerler eğitimi alanında Türkiye'de ilk bilimsel dergi olan Değerler Eğitimi Dergisi'nin ve dergide yayımlanan makalelerin bibliyometrik profilini belirlemek amaçlanmıştır. Araştırma nitel araştırma desenlerinden durum ça… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…When the literature on the subject was examined, it was observed that the doctoral dissertations in the field of values education in Turkey were similar to the results of the research and that there had been a noticeable increase in the number of doctoral dissertations since 2009 (Gündüz et al, 2017). It was understood that the most increase in master's theses occurred in 2013, and the number of theses decreased in the following years (Kurtdede-Fidan & Öner, 2018), in the Journal of Values Education most of the articles published in 2015 and the number of articles also decreased in the following years (Karagöz & Şeref, 2019), the highest number of proceedings on the subject in the International Social Studies Education Symposium were presented in 2017 (Metin & Yılmazer, 2019). When this result is evaluated, it is thought that the Ministry of National Education's emphasis on values education and the fact that the subject is directly involved in the education programs implemented since 2005 has been effective in the increase in the number of articles published.…”
Section: E Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…When the literature on the subject was examined, it was observed that the doctoral dissertations in the field of values education in Turkey were similar to the results of the research and that there had been a noticeable increase in the number of doctoral dissertations since 2009 (Gündüz et al, 2017). It was understood that the most increase in master's theses occurred in 2013, and the number of theses decreased in the following years (Kurtdede-Fidan & Öner, 2018), in the Journal of Values Education most of the articles published in 2015 and the number of articles also decreased in the following years (Karagöz & Şeref, 2019), the highest number of proceedings on the subject in the International Social Studies Education Symposium were presented in 2017 (Metin & Yılmazer, 2019). When this result is evaluated, it is thought that the Ministry of National Education's emphasis on values education and the fact that the subject is directly involved in the education programs implemented since 2005 has been effective in the increase in the number of articles published.…”
Section: E Discussionsupporting
confidence: 81%
“…The number of articles with more than 3 authors was only 15. Karagöz & Şeref (2019) concluded that articles with a single author were the majority in their studies, in which they examined the articles published in the Journal of Values Education, while Metin & Yılmazer (2019) concluded that most of the papers presented at the International Social Studies Education Symposium were with two authors. In both studies, it was stated that the number of studies with 3 or more authors was very small in parallel with the results of the research.…”
Section: E Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FC model continues to exist today as a popular approach that continues to be used in education. It Today, there are bibliometric analysis studies in different disciplines (Alkan, 2014;Arici et al, 2019;Karagöz & Şeref, 2019;Yang, Sun & Liu, 2017;Zan, 2013). As the use of Vosviewer software makes it easier to visually express data while conducting bibliometrics analysis, it is an important tool for researchers who will perform bibliometrics analysis.…”
Section: Introductionmentioning
confidence: 99%